2013
DOI: 10.1002/alr.21249
|View full text |Cite
|
Sign up to set email alerts
|

Five‐degree, 10‐degree, and 20‐degree reverse Trendelenburg position during functional endoscopic sinus surgery: a double‐blind randomized controlled trial

Abstract: FESS in 20-RTP produced the best BS and lowest blood loss without compromising surgical technique.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
39
0
2

Year Published

2014
2014
2020
2020

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 47 publications
(43 citation statements)
references
References 25 publications
2
39
0
2
Order By: Relevance
“…Previous randomized controlled trials have examined the use of reverse Trendelenburg position in ESS and found that this position improves endoscopic visualization and decreases blood loss. 20,21 Regional anesthesia techniques such as pterygopalatine fossa injections with lidocaine and epinephrine may induce local nasal mucosal vasoconstriction and provide improved analgesia. 22,23 …”
Section: Discussionmentioning
confidence: 99%
“…Previous randomized controlled trials have examined the use of reverse Trendelenburg position in ESS and found that this position improves endoscopic visualization and decreases blood loss. 20,21 Regional anesthesia techniques such as pterygopalatine fossa injections with lidocaine and epinephrine may induce local nasal mucosal vasoconstriction and provide improved analgesia. 22,23 …”
Section: Discussionmentioning
confidence: 99%
“…In a randomized blinded trial, Humphreys & Hwang operating with the head of bed elevated at 20 offered optimized endoscopic visualization and lower blood loss than lesser degrees of head elevation. 28 Mucosal injections of the lateral nasal wall and middle turbinate with lidocaineepinephrine have long been endorsed as beneficial for reducing intraoperative bleeding. Although such injections are effective as a regional anesthetic block for endoscopic procedures performed under local anesthesia, their efficacy in reducing bleeding is less certain.…”
Section: Intraoperative Phasementioning
confidence: 99%
“…Mean arterial blood pressure may not be changed due to compensatory mechanism by centers in carotid and aortic bodies. Gan, et al [9] compared various degrees of head elevation (5°,10°,20°) and found that significant improvement in blood loss in the 20° group compared to 10°. Prolonged or excessive head elevation may cause brain ischemic events.…”
Section: Reverse Trendelenburgmentioning
confidence: 99%